Supersymmetric Radiative Flavour - Conlon, J; Pedro, F (2011)
We examine possibilities for the radiative generation of the Yukawa couplings and flavour structure in supersymmetric models in the supersymmetric phase. Not withstanding the non-renormalisation of the Wilsonian superpotential, this can occur through the 2-loop vertex renormalisation of the physical 1PI couplings. We describe this effect and construct models in which this occurs. For models attempting to reproduce the full flavour structure of the Standard Model, we analyse the tension between such models and constraints from low-energy flavour observables. We note that the tension is weakest for the case of generating Dirac neutrino masses.